Lot-splitting approach of a hybrid manufacturing system under CONWIP production control: a mathematical model - AĞLAN GÖKLER, CANAN (TAYLOR & FRANCIS LTD, 2015)
This paper discusses the advantages of lot splitting in hybrid manufacturing environments where cellular and functional layouts are combined under Constant Work in Process (CONWIP) production control. The proposed model fills a research gap in the related literature by applying lot splitting and pull production simultaneously. A linear CONWIP control mathematical model that minimises the average flow time is developed in case of lot splitting. The developed model has sequence-dependent set-up times. The demand level, coefficient of variation (CV) impact and set-up time reduction effect on CONWIP production control are also investigated. The model is solved using GAMS21.6 optimisation software; the optimal backlog list, the number and size of sublots are reported. The proposed model is compared with lot production under push control in different settings as well as with two different heuristics from the literature. Experimental results indicate that in all settings, the lot splitting is more advantageous than lot production in terms of average flow time. CV has a greater effect than set-up time reduction on average flow time.
Keywords: lot splitting; hybrid manufacturing; CONWIP production control; FLOW-SHOP; PROGRAMMING-MODEL; PRODUCTION LINES; TIME; DESIGN; WIP; JIT